Create a Research Space (CARS) in Introduction of Indonesian Bachelor Thesis: a Corpus-Based Analysis - Miftahulfadlik Dabamona; Dewi Elmiana Satria; Ariyani Fatimah; Sri Rahayu (Journal of English Education and Teaching, 2022)
Bachelor Thesis (BT) is the requirement for university students to obtain a degree. The Introduction chapter, to some extent, becomes a challenging task to do, like the role that it upholds. Swales (2004), on his model of Create-a-Research-Space (CARS), has given a guideline in composing the introduction chapter using three moves: establishing a territory, establishing a niche, and occupying the niche. This study aims to analyze 32 BT’s introduction chapter in one of English Major of State Islamic Colleges in Indonesia by employing CARS model as the framework. Also, the lexical signal in the rhetorical structure is considered. The results demonstrated that the moves occurrences do not thoroughly perform the rhetorical structure given in the CARS model. This study suggests that academic writing is necessary for students to seek a higher-education path must be equipped with an awareness of structuring arguments. To become successful academic writers, undergraduates need to improve their linguistic competence, syntactic fluency, and lexical capacity to write analytically, competently, and persuasively.